(3GdEaUGM aj GdYhjUs - (3fUjQ GdOjf Hf GSOs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aEfffi CWGd Gddg HbGc hLFJ HgG Ydi MQha GdeYLe TjFkG aTjFkG hChQOJ JMJ cd HjJ efgG eG jMJedg ef JaSjQ eYfi hJQJjH daX hJhLjg EYQGH MQa GdgeRI s
(3BNQgG (B:s
(3Ndjdi Efi HGdYdi LO YGdb fgGQi hjWHjfi EdjgG GdeSGYjG agPg CNdGb GdYdeGA heG ShGgG aeWQM heOhd Jbhd Hg GdLGd Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3JJHY ajgG GdeDda GdcJH GdZQjHI hGSJNQL efgG GdCHjGJ GdYLjHI aChVM EYQGHgG hPdd UYGHgG HYO ZehV eYGfjgG hObI GdEYQGH ajgG Ke Efg jPcQ GdHjJ Ch GdHjJjf Ke jYQHgG EYQGHkG TGajkG hjYddg JYdjdkG cGajkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(386) s
Keywords: (3GdCOHs